Perceived Values of Zonguldak Central Scrubber Area as an Alternative Approach to Preservation of Industrial Heritage - Nilay Nida Can; Müge Akkar Ercan (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Zonguldak, a modern industrial city in Turkey, has witnessed the highest social life and production style, urban architecture, and socio-economic relations in the 20th century. As a prominent industrial symbol in the city, the Zonguldak Central Scrubber Area has become idle with the neoliberal economy. This paper focuses on the values of this site by examining the pre- and post-industrialization status. As a methodology, conceptual and value mapping have been conducted on the data, of which both 10 semi-structured in-depth interviews with three stakeholder groups: decision-makers, site employees, and researchers and archival data. This approach presents technological, document, socio-cultural, political, aesthetic, symbolic, identity, and economic values between 1970s and 2000s. The mixed method analysis of interviews emphasizes the organic role of the stakeholders in the preservation process. The importance of the study is to reveal the multi-dimensional character of Zonguldak's industrial heritage through place-based values.